4(x-5)=5(x+6)

Simple and best practice solution for 4(x-5)=5(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-5)=5(x+6) equation:


Simplifying
4(x + -5) = 5(x + 6)

Reorder the terms:
4(-5 + x) = 5(x + 6)
(-5 * 4 + x * 4) = 5(x + 6)
(-20 + 4x) = 5(x + 6)

Reorder the terms:
-20 + 4x = 5(6 + x)
-20 + 4x = (6 * 5 + x * 5)
-20 + 4x = (30 + 5x)

Solving
-20 + 4x = 30 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-20 + 4x + -5x = 30 + 5x + -5x

Combine like terms: 4x + -5x = -1x
-20 + -1x = 30 + 5x + -5x

Combine like terms: 5x + -5x = 0
-20 + -1x = 30 + 0
-20 + -1x = 30

Add '20' to each side of the equation.
-20 + 20 + -1x = 30 + 20

Combine like terms: -20 + 20 = 0
0 + -1x = 30 + 20
-1x = 30 + 20

Combine like terms: 30 + 20 = 50
-1x = 50

Divide each side by '-1'.
x = -50

Simplifying
x = -50

See similar equations:

| 7x-22=6 | | x-7/5x-8 | | =8(2x-3) | | 6x*6+3x*3=5x-2+2x*2 | | 7t-11t=16 | | 3x+4+2x+1=4+x | | 7-2+1-2x-5+3x=11-x | | -6(x+5)=66 | | 90=-6+8(p+4) | | (5n^2-n+6)+(8n^2-11)=0 | | 6+3=8x+4 | | -36+y=-2 | | -6(6x+8)=-36+48 | | 14y=350 | | 12x+13=115 | | 15y/12y^5 | | 0.3x-1=0.32 | | 5x*3-8+2x-4=2+3x*6 | | 120/10=-3y | | -12=-2.5x-3 | | 4-x+8=6 | | 2x+2x+3=-7 | | 0.5x+0.16=0.75 | | 6k^2-53k-9=0 | | 4x*6=8x-1 | | 4(x+9)=-24 | | 0.5x+6=0.75 | | -30=9/-5 | | 2-2n=3n+10 | | 4d-3=d+42 | | 5(N+1)=-2n+4(n-4) | | X-7+20=7x-10 |

Equations solver categories